2016
DOI: 10.1111/mcn.12369
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of perceived insufficient milk among new mothers in León, Nicaragua

Abstract: Breastfeeding has been shown to improve maternal and child health. In Nicaragua, the primary risk of death and disability-adjusted life years among children under 5 years of age is suboptimal breastfeeding. Although the Nicaraguan Ministry of Health promotes exclusive breastfeeding from within the first half hour through the first 6 months of life, less than a third of children in the country under 6 months of age are exclusively breastfed. As part of a larger, mixed-methods study, 21 semi-structured, in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 19 publications
5
24
1
5
Order By: Relevance
“…In our adjusted analysis of exclusive breastfeeding, we found that mothers who reported that their infant had been large at birth were less likely to exclusively breastfeed for 6 months. This association, similar to our finding of prelacteal feeds and suboptimal initiation of breastfeeding, may in part be mediated by fears of insufficient milk supply (Safon et al, ). Mothers who have babies they perceive as large may believe that their child needs more milk than they can provide, and therefore try to supplement breast milk with other substances.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our adjusted analysis of exclusive breastfeeding, we found that mothers who reported that their infant had been large at birth were less likely to exclusively breastfeed for 6 months. This association, similar to our finding of prelacteal feeds and suboptimal initiation of breastfeeding, may in part be mediated by fears of insufficient milk supply (Safon et al, ). Mothers who have babies they perceive as large may believe that their child needs more milk than they can provide, and therefore try to supplement breast milk with other substances.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we are unaware of research exploring this relationship in any Central American population. Due to the centrality of culture in choices about breastfeeding, country-specific data could guide national policy interventions in Nicaragua and other Central American countries (Safon et al, 2016;Sarat Chandra, Sri Hari, & Susheela, 2015).…”
mentioning
confidence: 99%
“…In contrast to other studies in Nicaragua and Latin America no demographic factors nor reporting insufficient time to breastfeed or insufficient breastmilk supply were found to correlate with early cessation of breastfeeding [5,7]. Surprisingly, more mothers who exclusively breastfed reported pain than those who discontinued earlier also in contrast to previous studies [6,17]. These mothers may have had more realistic expectations of breastfeeding to begin with, Fig.…”
Section: Discussioncontrasting
confidence: 79%
“…Among limitations of this study, the potential for acquiescence bias was recognised, whereby participants tend to respond positively to neutral questions, as well as social desirability bias, where answers that are perceived to be more acceptable than true attitudes or behaviours may be given (Kaminska & Foulsham, ; Ross & Mirowsky, ). A recent study in Central America has suggested that a physical inability to breastfeed might be considered an acceptable justification for early initiation of complementary feeding but that women may be unwilling to discuss reasons for not wanting to breastfeed (Safon et al, ). By identifying herself with her disciplinary background as a veterinarian, the primary investigator in the present study sought to minimise association with medical personnel, with whom nonadherence to IYCF guidelines has been suggested to be less likely to be shared (Mabilia, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Central America has suggested that a physical inability to breastfeed might be considered an acceptable justification for early initiation of complementary feeding but that women may be unwilling to discuss reasons for not wanting to breastfeed (Safon et al, 2017). By identifying herself with her disciplinary background as a veterinarian, the primary investigator in the present study sought to minimise association with medical personnel, with whom nonadherence to IYCF guidelines has been suggested to be less likely to be shared (Mabilia, 2005).…”
Section: Discussionmentioning
confidence: 99%